The Site-Specific Recombination System of the Escherichia coli Bacteriophage Φ24B - Mohaisen, Mohammed Radhi; McCarthy, Alan John; Adriaenssens, Evelien M.; Allison, Heather Elizabeth (Frontiers in Microbiology, 2020)
Stx bacteriophages are members of the lambdoid group of phages and are responsible for Shiga toxin (Stx) production and the dissemination of Shiga toxin genes (stx) across shigatoxigenic E. coli (STEC). These toxigenic bacteriophage hosts can cause life-threatening illness, and Shiga toxin (Stx) is the virulence determinant responsible for the severe nature of infection with enterohemorrhagic E. coli (EHEC), a subset of pathogenic STEC. Stx phages are temperate, and in the present study the identification of what is actually required for Stx phage Φ24B and bacterial DNA recombination was tested using both in vitro and in situ recombination assays. It is well established that phage , which underpins most of what we understand about lambdoid phage biology, requires its own encoded phage attachment site (attP) of 250 bp, a host encoded attachment site (attB) of 21 bp and a host encoded, DNA binding protein known as integration host factor (IHF). The assays applied in this study enabled the manipulation of the phage attachment site (attP) and bacterial attachment site (attB) sequences, and the inclusion or exclusion of a host-encoded accessory element known as integration host factor. We were able to demonstrate that the minimal attP sequence required by Φ24B phage is between 350 and 427 bp. Unlike phage , the minimal necessary flanking sequences for the attB site do not appear to be equal in size with a total length between 62 and 93 bp. Furthermore, we identified that the Φ24B integrase does not require IHF to drive the integration and recombination process. Understanding how this unusual Stx phage integrase works may enable exploitation of its promiscuous nature in the context of genetic engineering.